Vertical transmission and kinetic of antibodies anti-Neospora caninum in naturally infected lambs in the semiarid region of Brazil - Feitosa,Thais Ferreira (2021)
Abstract Aimed with this study to evaluate vertical transmission of Neospora caninum in naturally infected sheep and to monitor the kinetics of antibodies against this protozoon in their lambs. Therefore, 48 pregnant ewes, from five herds, were divided into two groups: G1 - positive for anti-N. caninum antibodies, with 19 animals; and G2 - seronegative, with 29 animals. Blood samples were taken from the ewes and their lambs, immediately after birth, before ingesting colostrum, and 2, 7, 14, 21, 28, 35, 42, 49 and 56 days after birth. Analysis on serum antibodies was performed using the indirect immunofluorescent antibody test. Among the 19 seropositive mothers, six (31.6%) gave birth to lambs seropositive before ingesting colostrum and it was found that these lambs remained positive until the end of the study (56 days). Only one of the lambs, from a ewe that presented an antibody titer of 200, seroconverted after ingestion of colostrum. All the lambs that had been born from negative mothers remained negative throughout the experimental period. It was concluded that transplacental transmission was an important form of diffusion of N. caninum in the herds studied and that seropositive lambs maintained circulating antibodies during the period analyzed.